Eficiência da osmose reversa no tratamento de água de poços salobros e salinos em comunidades e assentamentos rurais do Oeste Potiguar - Antas, Francisco Pio de Souza (Universidade Federal Rural do Semi-Árido, 2017)
In the semi-arid region, due to the predominance of the crystalline basement, the ground waters usually have high concentration of salts. To make these waters suitable for consumption, desalination plants have been installed in rural communities and settlements to meet the water demand. However, regardless of the efficiency of the membrane and installed structure of the desalinators, the reverse osmosis system will always produce not only potable water, but also a residue (brine or concentrated reject) with salt concentration higher than that of the original water. Our first objective was to investigate the efficiency of reverse osmosis in the purification of water from brackish and saline wells in desalination plants installed in Rural Communities and Settlements in Western Rio Grande do Norte. Second, we aimed was to study hydrochemical properties of the waters from the desalination process (well water, saline reject and purified water). The third objective was to propose a relative quality index for the waters from the reverse osmosis treatment plants for irrigation purposes. Four campaigns were carried out to collect samples of well water, purified water and reject brine, from October 2013 to November 2014, in 7 inland desalination plants of Rural Communities and/or Settlements in Western Rio Grande do Norte. The following parameters were determined: reverse osmosis efficiency in water purification and the quality parameters electrical conductivity (EC), pH, cations (sodium, potassium, calcium and magnesium) and anions (chloride, carbonate and bicarbonate), Sodium Adsorption Ratio (SAR), Langelier Saturation Index (LSI), Ryznar Stability Index (RSI) and Calcium/Magnesium ratio. In addition, the influence of LSI and RSI on the recovery rate of the reverse osmosis desalination systems was also investigated. The analyses of the results indicate that the mean recovery rate of the desalination systems was equal to 32.11% for October/November 2013, 52.42% for February/March 2014, 41.41% for June/July 2014 and 33.60% for October/November 2014. High values of Index Assessment of a desalination plant's water quality are shown as possible delineators of risk of soil salinization and groundwater deterioration. The highest degree of land use impact upon on the water quality from desalination plant was recorded in reject brine samples followed by well water. As to the classification of the waters, 17.86% of the analyzed water samples were classified as excellent (Class I), 22.62% as good (Class II), 22.62% as intermediate (Class III), 10.71% as poor (Class IV) and 26.19% as very poor (Class V)
Keywords: Irrigação; Eficiência de dessalinizadores; Índice de qualidade de água; Irrigation; Efficiency of desalinators; Water quality index; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO